Kokand Free Economic Zone - Zhobborov Azam Mashrabovich; Tojiboeva Mahliyo Azamzhon kizi; Karimov Shoulug Zokirjon ugli (International Journal on Human-Computing Studies, 2022)
This scientific article provides important, interesting economic and geographical information about the Kokand Free Economic Zone, one of the important industrial centers that makes a significant contribution to the economic and social well-being of Uzbekistan, and the international economic zones in the world.